Konsep Pemikiran Pendidikan Sufisme Menurut Ibnu Athaillah As-Sakandari Studi Kitab Al-Hikam - Muhammad Ibnu Faruk Fauzi (Badan Penerbit STIEPARI Press, 2022)
Ibn Athaillah is a figure of the Shadziliyah order, where syadziliyah is one of the leading Sufi orders in the world, especially in Indonesia. Ibn Athaillah was a prolific scholar with his works in the fields of interpretation, Sufism, hadith, aqidah, nahwu, and ushul fiqh. One of his best known works in the field of Sufism is the book of Al-Hikam. Al-Hikam is a popular book among Muslims. The Book of Al-Hikam is the main work of ibn Athaillah which has been very popular in the islamic world for centuries to the present day. This book is also the main study of almost all Islamic boarding schools in Indonesia. It contains wise words about morals, heart, and his relationship with the Khaliq, namely Allah Almighty. Ibn Athaillah in his study in the book of Al-Hikam with reference to the Qur'an and As-Sunah. The Book of Al-Hikam is a hallmark of Ibn Athaillah's thought, especially in terms of Sufism. This athaillah thought is not just a sufism style that prioritizes theology, but contains elements of shari'a experience, tarikat, and essence pursued in a methodical way.